Sugars in Antarctic aerosol. (October 2015) - Barbaro, Elena; Kirchgeorg, Torben; Zangrando, Roberta; Vecchiato, Marco; Piazza, Rossano; Barbante, Carlo; Gambaro, Andrea
Abstract: The processes and transformations occurring in the Antarctic aerosol during atmospheric transport were described using selected sugars as source tracers. Monosaccharides (arabinose, fructose, galactose, glucose, mannose, ribose, xylose), disaccharides (sucrose, lactose, maltose, lactulose), alcohol-sugars (erythritol, mannitol, ribitol, sorbitol, xylitol, maltitol, galactitol) and anhydrosugars (levoglucosan, mannosan and galactosan) were measured in the Antarctic aerosol collected during four different sampling campaigns. For quantification, a sensitive high-pressure anion exchange chromatography was coupled with a single quadrupole mass spectrometer. The method was validated, showing good accuracy and low method quantification limits. This study describes the first determination of sugars in the Antarctic aerosol. The total mean concentration of sugars in the aerosol collected at the "Mario Zucchelli" coastal station was 140 pg m −3 ; as for the aerosol collected over the Antarctic plateau during two consecutive sampling campaigns, the concentration amounted to 440 and 438 pg m −3 . The study of particle-size distribution allowed us to identify the natural emission from spores or from sea-spray as the main sources of sugars in the coastal area. The enrichment of sugars in the fine fraction of the aerosol collected on the Antarctic plateau is due to the degradation of particles during long-range atmospheric transport. The composition of sugars in the coarse fraction was also investigated in the aerosol collected during the oceanographic cruise. Highlights: A sensitive HPAEC-MS method was developed to analyze a wide range of sugars. This is the first study on the sugars composition of the Antarctic aerosol. The particle-size distribution of sugars allowed us to identify their sources. The behavior of atmospheric sugars was also investigated far from emission sources.